Temperature and immigration effects on quorum sensing in the biofilms of anaerobic membrane bioreactors. (1st September 2021) - Tabraiz, Shamas; Petropoulos, Evangelos; Shamurad, Burhan; Quintela-Baluja, Marcos; Mohapatra, Sanjeeb; Acharya, Kishor; Charlton, Alex; Davenport, Russell J.; Dolfing, Jan; Sallis, Paul J.
Abstract: Quorum sensing (QS), a microbial communication mechanism modulated by acyl homoserine lactone (AHL) molecules impacts biofilm formation in bioreactors. This study investigated the effects of temperature and immigration on AHL levels and biofouling in anaerobic membrane bioreactors. The hypothesis was that the immigrant microbial community would increase the AHL-mediated QS, thus stimulating biofouling and that low temperatures would exacerbate this. We observed that presence of immigrants, especially when exposed to low temperatures indeed increased AHL concentrations and fouling in the biofilms on the membranes. At low temperature, the concentrations of the main AHLs observed, N -dodecanoyl-L-homoserine lactone and N -decanoyl-L-homoserine lactone, were significantly higher in the biofilms than in the sludge and correlated significantly with the abundance of immigrant bacteria. Apparently low temperature, immigration and denser community structure in the biofilm stressed the communities, triggering AHL production and excretion. These insights into the social behaviour of reactor communities responding to low temperature and influx of immigrants have implications for biofouling control in bioreactors. Graphical abstract: Image 1 Highlights: Low temperature and cell immigration affect QS activity mainly in the biofilm. Temperature and cell immigration did not affect AHL levels in the mixed liquor. AHL levels were higher at 4 °C than at 15 °C in AnMBR biofilms. At low temperature core community and immigrant cells respond with C10-HSL and 12-HSL. Immigrant-rich membranes tend to foul faster at 4 °C than immigrant-free ones.